Food for Health, Food for Wealth : Ethnic and Gender Identities in British Iranian Communities. - Harbottle, Lynn (Anthropology of Food & Nutrition., 2000)
Food and eating practices are central to current sociological and anthropological concerns about the body, health, consumption, and identity. This study explores the importance of these themes as they intersect with processes of globalization and cultural production within a specific group of consumers, British Sh''ite Iranians. Through the analysis of the consumption practices of this particular migrant group, this book illustrates how both the nutritional value and symbolic significance of food contribute to its health-giving properties and how gender and ethnic identities are preformed and.